Implementasi Privacy Module Menggunakan Algoritme Enkripsi Trivium Pada SNMPL8 - Dimas Dwi Radhityo; Ari Kusyanti; Widhi Yahya (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Device management is needed when more internet of things (IoT) devices are connected in a network. One of the device management protocols is SNMP. But SNMP generates large data. Therefore there is a monitoring system that developed for effectivity in generating data called SNMPL8. On the other hand, SNMPL8 did not focus on security functions. One of the security functions for monitoring systems is the SNMPv3's Privacy Module. However, the Privacy Module still using CBC-DES algorithm that is not recommended by NIST, so a replacement algorithm is needed. One of the candidates is Trivium algorithm that designed for constrained devices. Therefore, this study uses the Trivium algorithm adopted on the SNMPv3's Privacy Module for network monitoring systems. Based on the getResponse testing, the Privacy Module requires 17.28 ms to generate keystream and 2.76 ms for the encryption process. The difference in memory at implementation is 176 Bytes, while the difference in the total data package is 769 Bytes.